FOMO, Social Validation and Impulse Buying in Live Streaming E-Commerce - Zhang, Xiaochen; Rosli, Nadzirah (Journal of Ecohumanism, 2025)
Due to extreme marketing exposure, live streaming and e-commerce are now being merged as a unique marketing platform. Recently, some studies have identified how live streaming has increased consumer impulse purchase behaviour. They found FOMO (Fear of Missing Out) is the primary factor that drives this behaviour. However, despite live streaming being a social media phenomenon, social validation was overlooked by many authors as an organism. This study conducted a primary survey among 467 Chinese participants within an empirical design setting. A structural equation model reveals that, apart from FOMO, social validation is also a significant factor that drives impulse purchase behaviour. Some stimuli, such as visual appeal, price, and product varieties, were also tested. FOMO and social validation were found to mediate these stimuli. Overall, impulse purchase behaviour in live streaming is a combined phenomenon of FOMO and social validation.